Assessment of the Perceived Relationship Between Healthy Nutrition and Cardiovascular Diseases by the Adult Czech Population - Olišarová, Věra; Tóthová, Valérie; Šedová, Lenka; Bártlová, Sylva; Chloubová, Iva; Michálková, Helena; Prokešová, Radka; Trešlová, Marie (Adis, 2019)
Cardiovascular diseases constitute one of the main causes of disability and premature death. The basic pathology consists of atherosclerosis. Therefore, influencing risk factors, including nutrition, is essential for prevention. AIM: To assess the opinion of Czech citizens, over 40 years old, on the role of nutrition as it relates to risk factors for cardiovascular diseases. METHODS: Data from 1992 participants were acquired using a research questionnaire administered throughout the Czech Republic from 1.4.2016-20.4.2016. The data was analyzed using the SASD program, version 1.4.12. RESULTS: Data analyses revealed that the age group in question still includes a great number of people who are unaware of the relationship between nutrition and development (31.8%) or progression (18.0%) of heart diseases. Rejection of the relationship was most frequently expressed by those 40-49 years of age and those that were employed. The study also found that the role of nutrition modification was more frequently discussed between patients and physicians (54.7%) than patients and nurses (38.0%). An overwhelming majority of respondents considered information related to nutrition modification useful (93.0%). CONCLUSION: In order to increase the efficiency of preventive measures, the transfer of theoretical knowledge to the lay public must be accompanied by interventions aimed at information repetition, motivation, and establishment of partnerships with health care providers.
Vnímání vztahu mezi zdravou výživou a kardiovaskulárními chorobami českou populací
Keywords: Cardiovascular diseases; Nurse; Nutrition habits; Prevention; Risk factor; Kardiovaskulární choroby; Sestra; Výživové zvyklosti; Prevence; Rizikové faktory